SNF nursing and therapy collaboration : optimizing compliance, reimbursement, and documentation - Brewer, Kate; Lang, Theresa A. (HCPro, 2013)
This book includes documentation strategies for both nurses and therapists. It shows how to align resident documentation across multiple disciplines to improve quality of care and protect organizations from an audit.